IMPLEMENTASI PENGEMBANGAN INOVASI PEMASARAN DIGITAL DALAM MENINGKATKAN EFEKTIVITAS PENJUALAN PRODUK LOKAL DI KOTA SERANG - Sucihati, Sucihati; Fidziah, Fidziah; Endrawati Subroto, Esty (Yayasan Education and Social Center, 2024)
This community service activity aimed to enhance the digital marketing capabilities of small and medium enterprises (SMEs) in Serang City. Conducted over two weeks in September 2024, the training covered essential topics in digital marketing, focusing on social media and e-commerce platforms as tools for expanding market reach and increasing product sales. More than 30 participants, representing various types of SMEs, gained practical skills in creating business accounts, managing social media platforms, and utilizing online advertising to improve product visibility. Despite initial challenges, participants successfully implemented strategies that led to increased market access and sales growth. The program received positive feedback, with many businesses reporting expanded customer bases beyond local markets. This initiative highlights the critical role of digital marketing in enhancing the competitiveness and sustainability of SMEs in the digital era.